PET (Polyethylene Terephthalate) depolymerization method
By using a PET depolymerization method using a choline ionic liquid catalyst, the problem of PET depolymerization in the prior art is not attractive on industrial scale using (2-hydroxyethyl) trimethylammonium arginate ionic liquid. , realizes efficient PET depolymerization and repolymerization under low temperature and low pressure, provides the possibility of reuse of PET monomers, and has the advantages of production and environment.
Patent Information
- Application Number
- CN202380027895.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2023-03-15
- Publication Date
- 2024-12-13
AI Technical Summary
When the existing PET depolymerization method uses choline ionic liquids on an industrial scale, the pressure and temperature conditions are not attractive, resulting in no industrial value in practical applications.
By designing a PET depolymerization method based on choline-based ionic liquid catalyst, using (2-hydroxyethyl)trimethylammonium arginine ([Cho][Arg]) ionic liquid, combined with glycolysis technology, Depolymerization and repolymerization of PET are carried out to prepare efficient PET monomers.
It realizes efficient PET depolymerization under lower temperature and pressure conditions, provides the possibility of reuse of PET monomers, and can be effectively depolymerized under ambient temperature and pressure, with the advantages of production and environment.
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This patent application claims the priority of Italian Patent Application No. 102022000005180 filed on March 16, 2022, the entire disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a process for the depolymerization of PET and the preparation of specific ionic liquids necessary for the depolymerization process. Background Art
[0004] Polyethylene terephthalate (PET) is one of the most widely used polymer materials because of its characteristics in terms of electrical properties, chemical resistance, performance at high temperatures and molding speed. In this regard, PET has long been the main material used in the food packaging industry. In fact, PET packaging is now commonly used in the production of trays in addition to bottles. In particular, the characteristics that contribute to making PET a very suitable material for food packaging include effective recycling loops in almost all continents and high material utilization from the recycling loops.
[0005] In this respect, polyethylene terephthalate can be processed by chemical recycling or mechanical recycling.Chemical recycling consists in deagglomerating the product powder by converting the polyethylene terephthalate into initial raw materials.
[0006] While chemical recycling allows PET powder to be returned to its monomeric state for subsequent reuse in the production of PET also for food use, mechanical recycling produces lower quality products, but at the same time is much cheaper. For example, with the exception of mineral water and soft drink containers according to special methods, the products resulting from mechanical recycling cannot be used in the food industry.
[0007] One way to perform chemical recycling involves depolymerization through glycolysis. Glycolysis is a chemical recycling method that converts waste PET into monomers through various chemical reactions. The most obvious advantage of glycolysis over other recycling methods is that the monomers can be repolymerized into new PET materials under relatively mild reaction conditions and low volatility solvents.
[0008] In recent years, the depolymerization of PET by glycolysis has been achieved using ionic liquids (ILs) as catalysts. Ionic liquids are organic salts with low melting points and are considered safer alternatives to traditional organic solvents due to their low vapor pressure and non-flammability. Naturally occurring aliphatic cationic ionic liquids, such as (2-hydroxyethyl)trimethylammonium, also known as choline, have attracted great attention.
[0009] The methods developed so far for depolymerizing PET using ionic choline liquids provide pressure and temperature conditions that make them unattractive when applied on an industrial scale.
[0010] Therefore, there is a perceived need to make available a process for depolymerizing PET using choline ionic liquids, the technical features of which make it more industrially attractive than the processes of the prior art. Summary of the invention
[0011] The inventors of the present invention have achieved a method that can meet the above needs.
[0012] Two and a half years ago, the inventors of the present application designed the PET depolymerization method according to the present invention. At that time, choline-based ionic liquids began to take their first steps through publications that mainly focused on their chemical-physical characterization, which was still insufficient in possible applications.
[0013] Only in the spring of 2020 was the first paper published that revealed the possibility of using choline-based ionic liquids as catalysts in a process for the depolymerization of PET by means of glycolysis (where, furthermore, the catalytic function had not yet been clearly demonstrated). To date, all publications related to the use of choline-based ionic liquids as catalysts in the glycolytic depolymerization of PET have not shown any particular developments.
[0014] Instead, during the period from August 2019 to March 2021, the inventors of the present application tested their technique first with multiple computational simulations (until December 2020) and then through laboratory experiments (until August 2021).
[0015] The object of the present invention is a PET depolymerization process, the essential features of which are reported in the independent claim 1 and the secondary and auxiliary features of which are reported in the dependent claims 2 to 6.
[0016] A further object of the present invention is a process for preparing an ionic liquid for use in the depolymerization process according to the invention, the essential features of which are reported in independent claim 7 and the secondary and auxiliary features of which are reported in dependent claims 8 and 9.
[0017] A further object of the present invention is an ionic liquid consisting of (2-hydroxyethyl)trimethylammonium argininate [Cho][Arg] prepared according to the invention. DETAILED DESCRIPTION
[0018] The embodiments shown below are for illustrative and non-limiting purposes only.
[0019] Synthesis of Choline Arginine Salt (Cho-l-Arg) Ionic Liquid
[0020] 0.70 grams of the highest purity l-arginine powder available was introduced into a 20 ml vial and a magnetic stirrer of appropriate size.
[0021] 1 ml of an aqueous solution of 2-hydroxy-N,N-trimethylethylammonium (ChoOH) was added dropwise to the vial. The amount of ChoOH added represented the number of moles equal to the number of moles of l-arginine. In addition, 7 ml of MilliQ water was also added to the vial. At this point, a constant rotation of 350 rpm was set on a magnetic stirrer while the vial was maintained at a temperature of 30° C. by means of a thermostatic bath. These conditions were maintained for a time interval of 48 h.
[0022] Adding the ChoOH aqueous solution directly to the l-arginine powder is necessary to prevent acid-base equilibration of the guanidinium group of the amino acid, which would make the metathesis reaction between the acid protons of the carboxyl group of the amino acid and the hydroxyl group of choline hydroxide more difficult.
[0023] It was demonstrated that if this addition was performed dropwise on an aqueous solution of l-arginine or in a single solution, maintaining an equal number of moles between l-arginine and choline hydroxide in both solutions, the yield of Cho-1-Arg was significantly reduced from 100% to about 30%. Subsequently, the contents of the vial were transferred to a 50 mL volumetric flask.
[0024] At this point, the water is removed by means of a rotary evaporator (pressure value of about 35-30 mbar), first keeping the water bath at 30° C., and then, after about 40% of the water has been removed, keeping the water bath at 40° C. The inventors of the present application believe that the step of removing water from the reaction matrix is necessarily a time-consuming process requiring great care. From the above, more than 0 to 3.5% of the compound by mass is obtained.
[0025] PET depolymerization
[0026] An example of depolymerization performed in the laboratory is reported below.
[0027] As will be immediately apparent to a person skilled in the art, the examples reported below are intended to demonstrate the effectiveness of the depolymerization of (2-hydroxyethyl)trimethylammonium arginine salt according to the process of the invention. In this respect, the reported yields should not be considered to be of particular importance, since they can be improved by cyclically repeating the process or by industrial adjustments that fall outside the characteristics defined in the claims.
[0028] 9.9936 g of PET from a transparent bottle and cut into pieces of approximately 1×0.5 cm size and 1.4108 g of ionic liquid consisting of (2-hydroxyethyl)trimethylammonium arginine salt ([Cho][Arg]) prepared as described above were introduced into a 50 ml reaction bottle.
[0029] The reaction bottle was fixed to a rotary evaporator with a constant temperature bath at 60°C to allow the viscosity of the ionic liquid to decrease and correspondingly increase the contact with the PET. Under these conditions, the rotary evaporator was started at a speed of 90 rpm and kept running for 90 minutes.
[0030] After 90 minutes, the temperature of the thermostatic bath was lowered to 30°C and the rotary evaporator was kept operating for a further 120 minutes.
[0031] After 120 minutes, the rotation was stopped and about 2 ml of methanol was added dropwise. After the methanol addition was complete, the rotation was restarted under the same conditions as above (90 rpm and 30° C.). After only 30 minutes of rotation (without the addition of methanol), the rotation was stopped and another 2 ml of methanol was added dropwise. After the methanol addition was complete, the rotation under the above conditions was restarted for another 30 minutes.
[0032] Repeat this operation 10 times.
[0033] According to a further embodiment, alkali metal methoxide can also be added together with the methanol.
[0034] After the addition of methanol was complete, the rotation itself was stopped and the undepolymerized PET was recovered by a Buchner funnel and washed with methanol for 10 minutes under moderate stirring. The washed methanol was then recovered and added to the depolymerization matrix consisting of white precipitate, [Cho][Arg] and methanol.
[0035] The undepolymerized PET was subsequently washed, dried appropriately and weighed. It was thus confirmed that the undepolymerized PET weighed 9.0105 g. A depolymerization yield of about 10% can be inferred from the above.
[0036] 20ml MilliQ water is added to the depolymerization matrix, and the rotation of 90rpm is restarted until the white precipitate is completely dissolved. At this point, the content of the reaction bottle is poured into a beaker together with an additional 150ml MilliQ water and a stirring rod. The beaker is contained in a crystallizer equipped with an ice bath, and the beaker is rotated at a speed of 500rpm for 15 minutes.
[0037] Subsequently, 1 M HCl solution was added dropwise to the beaker until the solution in the beaker reached pH 1. Under these conditions, the formation of a white precipitate was noted.
[0038] At this time, filter with a funnel and blue filter paper, and wash the white precipitate thoroughly with more MilliQ water. After recovery, dry the white precipitate by placing it in a crystallizer in an oven at a temperature of 94°C for 1 hour.
[0039] After drying, the white compound was subjected to 1H-NMR, ATR, and UV-Vis spectrophotometric analysis. As shown in the enclosed spectra, spectrophotometric analysis confirmed that the white compound was terephthalic acid.
[0040] The inventors of the present application believe that the procedure reported above is valid at any temperature that keeps the reagents in their liquid state. For this reason, it is believed that within the temperature range of -50°C to 70°C, the depolymerization process reported above can occur.
[0041] In the case where the depolymerization is carried out at a higher temperature than shown, a number of problems may be involved, such as degradation of the (2-hydroxyethyl)trimethylammonium arginine salt, dissolution of the monomeric reaction product (DMT) within the reaction matrix and subsequent slowing down of the depolymerization process and evaporation of the solvent (CH3OH).
[0042] Furthermore, as may be obvious to a person skilled in the art, the use of higher temperatures than indicated will inevitably lead to productivity problems if the process of the invention is applied on an industrial scale.
[0043] The inventors of the present invention believe that the optimal temperature range is 20°C to 40°C.
[0044] Furthermore, the inventors of the present invention believe that the ratio of PET to ionic liquid may be unbalanced with respect to both PET and ionic liquid without affecting the effectiveness of depolymerization.
[0045] Comparative Examples
[0046] For comparison purposes, three comparative examples were prepared in which [Cho][Gly], [Cho][Pro] and L-arginine were used instead of [Cho][Arg], respectively.
[0047] - Example using [Cho][Gly]
[0048] In this example, 1.0830 g of [Cho][Gly] and 1.0980 g of PET were used.
[0049] The time and temperature conditions of the depolymerization example according to the above invention were repeated while adding a certain amount of methanol dropwise, 0.1 ml each time.
[0050] [Cho][Gly] was synthesized in the laboratory using the same synthetic procedure as in the case of choline arginine salt and described above. All reagents used were certified by Merck.
[0051] At the end of the depolymerization procedure, the recovered non-depolymerized PET was found to weigh 1.0989 g and was therefore 0.082% more than the PET initially used (within the weighing error of the balance).
[0052] As is clear from the above, the use of an ionic liquid consisting of [Cho][Gly] does not result in any depolymerization.
[0053] - Example using [Cho][Pro]
[0054] In this example, 1.1620 g of [Cho][Pro] and 1.0452 g of PET were used.
[0055] The time and temperature conditions of the depolymerization example according to the above invention were repeated while adding a certain amount of methanol dropwise, 0.1 ml each time.
[0056] [Cho][Pro] was synthesized in the laboratory using the same synthetic procedure as in the case of choline arginine salt and described above. All reagents used were certified by Merck.
[0057] At the end of the depolymerization procedure, the recovered non-depolymerized PET was found to weigh 1.0511 g and was therefore 0.0560% more (within the weighing error of the balance) than the PET initially used.
[0058] As is clear from the above, the use of an ionic liquid consisting of [Cho][Pro] does not result in any depolymerization.
[0059] - Example using L-arginine
[0060] In this example, 0.7084 g of L-arginine and 1.1021 g of PET were used.
[0061] The time and temperature conditions of the depolymerization example according to the above invention were repeated while adding a certain amount of methanol dropwise, 0.1 ml each time.
[0062] At the end of the depolymerization procedure, the recovered non-depolymerized PET weighed 1.1022 g.
[0063] As is clear from the above, the use of L-arginine (certified by Merck) did not produce any depolymerization.
[0064] From the above description, surprisingly, it appears that only the use of the ionic liquid [Cho][Arg] is able to obtain PET depolymerization under ambient temperature and pressure conditions. Such a result provides important production and environmental advantages. In fact, the process of the present invention allows PET to be depolymerized to obtain the starting monomers, which in turn can be polymerized again.
[0065] It is important to note that the process of the present invention, when applied to a material comprising PET, successfully extracts the PET by depolymerization, leaving the other constituent components of the material usable.
[0066] In this regard, an example of depolymerization of textile fibers performed in the laboratory is reported below.
[0067] - Example of depolymerization of textile fibers -
[0068] The textile fiber sample is loaded into the 50ml volumetric flask, and the textile fiber sample is composed of a heavy 0.7158g fabric sheet (composed of 65% polyester and 35% cotton) and 0.6260g of the ionic liquid composed of (2-hydroxyethyl) trimethylammonium arginine salt ([Cho][Arg]). After the mixing step between the ionic liquid and the textile fiber is carried out at 30 ℃ using the rotor of a rotary evaporator, 1ml of methanol (0.1ml per hour) is added in the subsequent nine hours. Rotation is stopped after each addition to allow methanol to be incorporated into the reaction matrix. Subsequently, another 2.4ml of methanol is introduced six times by directly loading 0.4ml. The rotor is temporarily interrupted when each addition is made.
[0069] The depolymerization reaction was then interrupted by adding MilliQ water (approximately 50 ml) to the reaction matrix.The residual sample was washed with double distilled water in a beaker and dried, resulting in a weight of 0.5331 g.
[0070] The reaction medium was then filtered by removing the cotton polymer residues. The PET monomer was then extracted by adding 1 M HCl until pH 1 was reached. The terephthalic acid was collected by filtration, dried in an electric oven and weighed, yielding a mass of 0.14766 g compared to the initial polyester mass of 0.46527 g.
[0071] Therefore, about 33% of the depolymerization on the PET textile fibers can be estimated.
Claims
1. A PET depolymerization method obtained by using an ionic liquid containing choline; the depolymerization method is characterized in that PET, an ionic liquid consisting of (2-hydroxyethyl)trimethylammonium arginine salt [Cho][Arg] and methanol are mixed together at a temperature ranging from -50°C to 70°C.
2. The method according to claim 1, characterized in that: The weight ratio between PET and the ionic liquid ranges from 10 to 0.
05.
3. The method according to claim 1 or 2, characterized in that: It comprises (a) a first mixing step during which PET is mixed with the ionic liquid consisting of (2-hydroxyethyl)trimethylammonium arginine salt [Cho][Arg] at a temperature ranging from 20°C to 70°C, and (b) a depolymerization step during which the mixture obtained from the mixing step is added with ROH alcohol and stirred at a temperature ranging from -50°C to 70°C.
4. The method according to any one of the preceding claims, characterized in that The alkali metal methoxide is added along with the methanol.
5. The method according to any one of the preceding claims, characterized in that The methanol was added dropwise to the mixture.
6. The method according to any one of the preceding claims, characterized in that The depolymerization step includes successively repeating methanol adding operations and mixing operations.
7. Method for preparing an ionic liquid for use in a depolymerization method according to one of the preceding claims; characterized in that it comprises an addition step during which an aqueous choline solution is added to the l-arginine powder; and a subsequent mixing step during which the mixture produced in the addition step is stirred for a time interval ranging from 12 hours to 72 hours; the addition step and the mixing step are carried out at a temperature ranging from 15° C. to 45° C.; the molar ratio between the choline and the l-arginine is from 0.5 to 2.
1.
8. The method for preparing an ionic liquid according to claim 7, characterized in that: The choline aqueous solution was added dropwise to the arginine powder.
9. The method for preparing an ionic liquid according to claim 7 or 8, characterized in that: It includes a water removal step after the mixing step; the water removal step is performed at a temperature equal to or lower than 40°C.
10. Ionic liquid consisting of (2-hydroxyethyl)trimethylammonium argininate [Cho][Arg] obtainable according to any one of claims 7 to 9.
